Infantile Hemangiomas and Beta-Blockers: 10 Years After Therapeutic Revolution - Kieselová, Katarína (2019)
Infantile hemangioma is the most common vascular tumor of childhood, characterized by an initial rapid growth in the first months of life and with gradual spontaneous involution in the first years. Despite its benign behavior and spontaneous regression, about 10% of infantile hemangiomas have a negative functional or cosmetic impact, thus requiring an effective treatment. In 2008, an accidental discovery of a favorable effect of propranolol, revolutionized the therapeutic approach of infantile hemangioma, consequently becoming the first-line treatment of this vascular tumor. In this article, we will briefly review the advances in the treatment of infantile hemangioma in the last decade and discuss the published research data regarding the clinical use of propranolol. In addition, other emerging treatments will be addressed, which may in the future extend the therapeutic armamentarium for infantile hemangioma.